Limb motions and body roll in skilled and unskilled front crawl swimmers - Keppenham, B. C.; Yanai, T. (Medicine & Science in Sports & Exercise, 1995)
The coordination of limb movements and body roll in skilled (S) and unskilled swimmers (U) was investigated. Specifically, the timing of the hand entry with respect to body roll, and the timing of the strong beat kick with respect to body roll were analyzed. Implications. The following are suggested as teaching ingredients for crawl stroke timing. 1. Roll the hips and shoulders as a unit and to a considerable degree (as much as 90 degrees). 2. The initiation of the arm pull should occur as the hand entry is made and timed with the shoulder (body) roll in the stroke. 3. The body roll and arm pull should be timed together. 4. Emphasize being on one's side in the first and middle portion of the underwater pull.